Evaluation of an OpenSees Layered Shell Model for Simulating Flexure-Controlled Reinforced Concrete Walls - Stokley, Joshua C (My University, 2023)
Reinforced concrete walls are used commonly in mid- and high-rise buildings to resist lateral loads; typically, concrete walls have three-dimensional configurations to maximize stiffness and strength and to accommodate architectural constraints. Seismic design, evaluation, and retrofit of concrete wall buildings often requires nonlinear analysis to predict performance, assessment of earthquake risk for regions and individual buildings often requires nonlinear analysis to predict damage, loss of functionality, and repair time and cost. The research present here used high-performance cloud-computing resources to calibrate an OpenSees model for simulating the earthquake response of planar walls. Jupyter notebooks were used to create and run OpenSees models of individual walls included in a published experimental dataset, and Jupyter notebooks were used to define error functions for the model calibration effort. Creation of an efficient research workflow was enabled by use of the NHERI SimCenter quoFEM software. Computational time was reduced by using cloud computing resources provided by the NHERI DesignSafe-CI facility. Results of the effort include recommendations for modeling walls to provide accurate simulation of response and the creation of the Jupyter notebooks can support future projects.
Thesis (Master's)--University of Washington, 2023
Keywords: Engineering; Civil engineering